EFFECT OF NPK COMPOUND FERTILIZER , FOLIAR APPLICATION OF IRON AND GIBBERELLIC ACID ON THE GROWTH AND YIELD OF SALEMY POMEGRANATE CULTIVAR (Punica granatum L.) 4. STUDY OF CONCENTRATION OF SOME MINERALS IN LEAVES AND BERRIES - Nabil M. Ameen Al-Imam (Mesopotamia Journal of Agriculture)
This investigation had been conducted in an special orchard in Al-Hawija town - Kirkuk governorate during 2005 and 2006 growing seasons in order to study the effect of NPK fertilizer and foliar application of iron and gibberellic acid (GA3) and their interactions on concentration of some minerals in leaves and berries of Pomegranate (Punica granatum L.) trees Salemy CV. (local variety) .Results of both seasons summarized as follows: Adding of the 880 kg NPK/Hec. caused a significant increasing the concentration of nitrogen and iron in leaves and fruit berries nutrient , while adding 440 Kg NPK/Hec. caused a significant increasing the concentration of phosphorus and potassium in leaves and fruit berries .The foliar application with 200mg Fe/l caused a significant increasing the concentration of nitrogen (in first season) and phosphorus and potassium in leaves and fruit berries in both seasons. The spraying with 100mg GA3/l caused a significant increasing the concentration of nitrogen (in first season) and potassium in leaves and fruit berries in both seasons. The spraying with 200 mg GA3/l caused a significant increasing the concentration of nitrogen (in second season) , phosphorus and iron leaves and fruit berries in both seasons. Interaction results were asserted that adding of the 440 kg NPK/Hec.+200mg Fe/l +100mg GA3/l caused a significant increased the concentration of nitrogen in leaves, adding 440 kg NPK/Hec.+200mg Fe/l+200mg GA3/l caused a significant increased the concentration of phosphorus in leaves and fruit berries, adding 440 kg NPK/Hec.+100mg Fe/l + 100 mg GA3/l caused significant increased of potassium in leaves and fruit berries, adding 880 kg NPK/Hec.+200mg Fe/l+200mg GA3/l caused a significant increased of iron concentration in leaves and fruit berries for both seasons .